ANALISIS NILAI TAMBAH PADA KLASTER INDUSTRI PENGOLAHAN IKAN TERI KERING DI PULAU PASARAN KOTA BANDAR LAMPUNG - Ayu, Bunga Woro; Ismono, R Hanung; Soelaiman, Achdiansyah (Jurnal Ilmu-Ilmu Agribisnis, 2013)
The purpose of this research was to analyze the added value of the anchovy processing industry.  This research was conducted by cencus method in Pasaran Island, District of Teluk Betung Barat of Bandar Lampung City.  This location was selected purposively for it is the center of salted anchovy fish producers in Bandar Lampung.  All of the 38 active salted fish producers were recruieted as respondents.  The data were analyzed qualitatively and by Hayami method. The results showed that the average value obtained from the processing of a kilogram of wet fish being processed to be dried anchovies was the highest in the west wind season that was Rp7,253.02 with the ratio of added value to the value of the product was 29.73 percent. It meant that of every Rp100.00 of the product would be obtained added value of Rp29.73.  The average of added value in the normal monsoon was Rp4,808.72 with the ratio of added value to the product was 25.20 percent.  In the eastern monsoon, the average added value was Rp4,801.30 with the ratio of the added value to the product was 27.11 percent. Thus, this dried anchovy processing industry cluster gave added value. Keywords : added value, dried anchovy, Hayami method,  processing industry